Comparison of retroperitoneal and transperitoneal surgical routes in laparoscopic nodal staging for locally advanced cervical cancers (FIGO IB3-IVA). Issue 9 (September 2022) - Pécout, Marie; Phalippou, Jérôme; Azaïs, Henri; Ouldamer, Lobna; Bolze, Pierre Adrien; Ballester, Marcos; Huchon, Cyrille; Mimoun, Camille; Akladios, Cherif; Lecointre, Lise; Raimond, Emilie; Graesslin, Olivier; et al.
Abstract: Background: This study compares morbidity and mortality associated with retroperitoneal and transperitoneal para-aortic lymphadenectomy (PAAL) for pretherapeutic nodal staging of locally advanced cervical cancers (FIGO IB3–IVA). Methods: Pre-, per- and postoperative data of patients treated for locally advanced stage cervical cancer between 1999 and 2018 in 12 French referral centers (FRANCOGYN Study Group) were retrospectively collected. Results: The study was conducted using a sample of 448 patients, of whom 223 (49, 8%) underwent retroperitoneal (group 1) and 225 (50, 2%) had transperitoneal PAAL (group 2). No differences were noted concerning clinical and histological characteristics between the two groups. Among these 448 patients, 23 (5, 1%) had an intraoperative complication (9 (2, 0%) in group 1 and 14 (3, 1%) in group 2, p = 0.28) and 47 (10, 5%) had a postoperative complication (22 (4, 9%) in group 1 and 25 (5, 6%) in group 2, p = 0.44), only one of which required revision surgery but the patient died. The length of hospital stay was significantly shorter in group 1 than in group 2 (3.97 versus 4.88 days, p < 0.001). There was no significant difference in mortality between the two groups; 34 of 223 patients in group 1 (15.3%) and 40 of 225 patients in group 2 (15.6%) died (HR = 0.968, 95% CI [0.591–1.585]). There was no significant difference in recurrence-free or overall survival between the two groups. Conclusion: Retroperitoneal PAAL appears as a valuable and safety surgical route for nodal staging in locally advanced cervical cancer compared with standard transperitoneal PAAL.